Third-Party Punishment or Compensation? It Depends on the Reputational Benefits - Li, Zhuang; Hu, Gengdan; Xu, Lei; Li, Qiangqiang (Frontiers in Psychology, 2021)
Third-party fairness maintenance has been widely found, and the reputational benefits is an essential motivation for it. Third-party fairness maintenance includes two methods: punishment and compensation, and the reputations of these two methods differ. Based on previous studies, we predicted that reputational differences and the preference between the punishment and compensation of third parties are affected by whether the third parties have the freedom to choose between the two methods. The present study includes two component studies. In Study 1, the participants acted as fourth parties who were the observers to third-party fairness maintenance. We presented to the participants a scenario in which third parties had made responses to unfair results of the dictator game. The participants were asked to rate the reputations of the third parties who had chosen different response methods. In Study 1a, the third parties chose between punish/compensate and keep, which was indicative of non-intervention (not freely chosen), while in Study 1b, the parties chose between punish, compensate, and keep (freely chosen). The results showed that there was no reputational difference between the two methods in Study 1a, but in Study 1b, the reputation of compensation was better than that of punishment. In Study 2, the participants acted as third parties. The participants were asked to choose a method to respond to an unfair result of the dictator game. There were two reputational contexts: secret (the choice would not be known by others) and open (the choice would be known by others). In Study 2a, the third parties chose between punish/compensate and keep, while in Study 2b, they chose between punish, compensate, and keep. The results showed that in Study 2a, under the two reputational contexts, the third parties had no preference between the two methods, while in Study 2b, they tended to choose to punish under the secret context, but tended to choose to compensate under the open context. This study systematically reveals an interaction between fourth parties and third parties around reputational benefits and provides insights for understanding the role of reputation in the evolution of third-party fairness maintenance.